PG&E group portrait - Unknown:::Creator::::::::::::
Photograph is a group portrait of men and women wearing PG&E tee shirts and caps. Some of them are holding PG&E balloons. There is a little girl holding a teddy bear on the left side of the photograph, another small child on the right side, and a Basset Hound in the middle of the first row.